Implementasi dan Evaluasi E-Rekrutmen dalam Proses Rekrutmen Calon Karyawan di PT. Prima Karya Sarana Sejahtera - Mutia Mawardah; Susan Dian Purnamasari; Febriyanti Panjaitan; Nia Oktaviani; Fatmasari Fatmasari; Evi Yulianingsih; Merzi Tamara Oktaviani (Lembaga Pengembangan Kinerja Dosen, 2024)
This dedication implements and evaluates the e-recruitment system at PT. Prima Karya Sarana Sejahtera to enhance the employee recruitment process. By employing a structured implementation method, from initial preparation to final evaluation, this dedication successfully introduces the integration of psychological assessments into the company's e-recruitment platform. Evaluation results indicate a significant improvement in HR team understanding and skills in using this new system, as well as enhanced efficiency in candidate selection. The final report and presentation of results to PT. Prima Karya Sarana Sejahtera management illustrate the benefits of implementing this technology in optimizing the recruitment process. With ongoing support and consultation, it is expected that this e-recruitment system will continue to deliver sustained positive impacts for the company. Keywords: e-recruitment, psychological assessment, student dedication, recruitment efficiency